2023
DOI: 10.1186/s12903-023-03194-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of enamel roughness after orthodontic debonding and clean-up procedures using zirconia, tungsten carbide, and white stone burs: an in vitro study

Abstract: Background The main goal of orthodontic debonding is to restore the enamel surface as closely as possible to its pretreatment condition without iatrogenic damage. This study aimed to compare the effects of different adhesive removal burs; zirconia burs, tungsten carbide burs, and white stone burs on enamel surface roughness. Materials and methods Total sample of 72 extracted premolars was randomly divided into three equal groups (n = 24) depending … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Similar results were reported by other studies [27,28]. Various studies have reported different degrees of enamel loss during the removal of residual adhesive material, ranging from a few micrometers to around 50 µm [28][29][30][31]. Enamel thickness is stated to range from 1500 µm to 2000 µm; accordingly, it was reported that enamel loss of around 60 µm is not considered detrimental to the tooth [32].…”
Section: Discussionsupporting
confidence: 84%
“…Similar results were reported by other studies [27,28]. Various studies have reported different degrees of enamel loss during the removal of residual adhesive material, ranging from a few micrometers to around 50 µm [28][29][30][31]. Enamel thickness is stated to range from 1500 µm to 2000 µm; accordingly, it was reported that enamel loss of around 60 µm is not considered detrimental to the tooth [32].…”
Section: Discussionsupporting
confidence: 84%
“…Similar to our results, Tenório et al[ 33 ] Shafiee et al[ 34 ], and Ulusoy [ 23 ] showed that the time spent for resin removal with the TC bur was shorter than polymer bur and white stones, respectively. On the other hand, Thawaba et al [ 15 ] reported that. Zirconia burs were more effective for adhesive resin removal than TC systems, causing the least surface roughness and enamel damage.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using G* Power software (v3.1.3; Franz Faul, Universität Kiel, Germany) which depends on the effect size = 0.80, an alpha value of 0.05, and a power of 95%. The result showed that at least 15 samples were required in each group based on the study conducted by Thawaba et al [ 15 ]. However, the sample size was raised to 20 samples for each study group.…”
Section: Methodsmentioning
confidence: 99%